Individuation in the Main Characters of J.K. Rowling’s HARRY POTTER Series - S. Ines Linando; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This paper examines the individuation of Potter and Voldemort in Harry Potter series. To be a holistic individual, a person needs to be individuated by managing their three main archetypes. The three main archetypes are persona, shadow, and anima or animus. Potter and Voldemort have to manage their archetypes their journey as human beings. Each of them has to know his persona including his appearance, behavior and role; confront his shadow; and balance his anima. In the end, Potter manages himself to be a individuated person who can lead a good life, while Voldemort fails to be an individuated person and, as a result, he died.